The Influence of Earnings Volatility and Market Risk on Stock Prices - Alfahira Nur Anggriani, Raden Dewanti; Ratia Pratiwi, Inugrah; Erfiansyah, Erfan (Greenation International Journal of Economics and Accounting, 2024)
Banks function as places for investors to invest their money, as well as places for consumers to save and obtain loans. The value of a bank can be seen from the circulating stock price. Because stock prices have the ability to represent the value of a bank. However, the stock prices of the Indonesian banking industry have declined in 2020–2022. The effect of the COVID-19 pandemic is the cause. In this case, it can be said that the company has failed to achieve its goal of optimizing shareholder welfare in order to provide high returns for investors. This study aims to examine the impact of market risk and income volatility on the stock prices of the banking industry in 2020-2022. The research method used is a quantitative method utilizing secondary data taken from financial statements and historical data published on the Indonesia Stock Exchange and Yahoo Finance. The sample size used consists of 34 banking sector companies listed on the Indonesia Stock Exchange from 2020 to 2022. For the hypothesis in this study, it was tested using a multiple linear regression model. And for the analysis results in the research that has been conducted, it is stated that income volatility has a significant negative impact on stock prices, and likewise, market risk has a significant negative impact on stock prices.